Studi Eksperimental : Analisis Proses Pencampuran Warna Pantone Green 2282 C Menggunakan Tiga Warna - Andhika Rizqullah Setiawan; Heribertus Rudi Kusumantoro; Yoga Putra Pratama (Pusat riset dan Inovasi Nasional, 2025)
This study aims to obtain a color mixing formula that matches the Pantone Green 2282 C color with a target value of ΔLab <1 using three basic colors. The method used in this study is an experimental method with a Pre-Test Post-Test design. The results of this study are that the Pantone Green 2282 C color ink can be formed from three basic colors including Yellow 570, Blue 800 and Red 003 inks. The selection of these colors is based on the Lab* value which shows that the three inks are able to produce the Pantone Green 2282 C color with a target value of ΔLab <1. In the process of mixing these colors, White 45 ink is needed to balance the three colors. The process of obtaining the Pantone Green 2282 C color through experiments that produce a total of 15 formulas. Where the T-14 formula with a composition of Yellow 570 (50%), Blue 800 (35%), Red (15%) and Medium (10%) was chosen because the target value of ΔLab <1 has been achieved..